Mechanochemical engineering of interfacial M-Ov-Ni sites in CeZrO/Ni catalysts for reinforced low-temperature CO2 methanation - Xiaopo Niu; Yeben Liu; Yining Xia; Xinyu Hu; Zhengguo Wang; Chuqiao Song; Quanli Ke; Xiaoli Wei; Guokai Cui; Qingfa Wang; Lili Lin; Hanfeng Lu (Chemical Engineering Journal, 2026)

The ss3a/be2b double mutant yields high resistant starch through cooperative regulation of starch fine structure in indica rice - Yining Ying; Jiayuan Chang; Zhongwei Zhang; Lin Zhang; Xuexue Wang; Chengqi Yan; Jinsong Bao (Carbohydrate Polymers, 2026)

Predictive gas recirculation control for CO2-modified atmosphere treatment in a full-scale concrete maize silo using conditional multi-step forecasting - Jie Lin; Kun Hu; Xiaoping Yan; Haoyu Wen; Xiaoyu Zhang; Yining Wu; Yuanyi Luo; Hongwei Xiao (Journal of Stored Products Research, 2026)

Intelligent aeration technologies in grain storage: A comprehensive review of multi-physics modeling and AI-driven control - Xiaoyu Zhang; Jiale Guo; Yanhong Liu; Yuanyi Luo; Shuanglin Wang; Deqing Wang; Jie Lin; Kun Hu; Haoyu Wen; Yining Wu; Xiaoping Yan (Journal of Stored Products Research, 2026)

Stage-aware, gas-led early warning of cotton smoldering: A stored-product safety review - Yining Wu; Yanguang Zhu; Jie Lin; Xiaoyu Zhang; Haoyu Wen; Xiaoshuan Zhang (Journal of Stored Products Research, 2026)

Engineering over-oxidized cu on CNTs for sensitive non-enzymatic glucose sensing and energy applications - Songxin Zhong; Rida Li; Hui Chen; Chao Xiao; Yining Lan; Qi-an Chen; Jian Li; Changqiang Feng; Shizhan Li; Hengchan Qi; Chi Gong; Zukun He; et al. (Chemical Engineering Journal, 2026)

Reliability Enhancement of Underwater Acoustic Communication in Dynamic Underwater Channels via Unequal-Rate Frequency–Phase Signaling - Yining Lin; Yupeng Tai; Chenghao Hu; Yonglin Zhang; Jun Wang; Haibin Wang (Journal of Marine Science and Engineering, 2026)
Underwater acoustic (UWA) channels are inherently complex, with pronounced variability arising from multipath propagation, time variability, Doppler effects, and nonstationary ocean conditions. Such variability often leads to unstable communication reliability when conventional single-carrier signaling and fixed reception strategies are employed. In practical UWA environments, performance degradation may occur when channel characteristics deviate from the assumed regime, thereby limiting system robustness. To address this reliability challenge, this study develops an unequal-rate frequency–phase keying (URFPK) signaling strategy that combines a low-rate frequency component with a high-rate phase component. A corresponding receiver structure is designed, employing parallel coherent and noncoherent processing to enhance robustness under dynamic channel conditions. In addition, a reduced-complexity noncoherent procedure is introduced to improve computational efficiency. Simulation results demonstrate substantially improved robustness under severe UWA distortions. Full-scale sea trials further validate the engineering effectiveness of the proposed approach, achieving communication success rate improvements of 18.62% and 9.39% over baseline schemes within short intervals and maintaining an overall success rate exceeding 91% over extended transmissions. These results indicate that the URFPK signaling strategy provides a practical and robust mechanism for improving UWA link reliability in dynamic UWA channels.

Rhodotorula mucilaginosa SY-AN-9 as a novel starter culture for improving the safety of Northeastern Chinese dried sausage: Mitigating N-nitrosamines and elucidating the underlying mechanism - Ying Yue; Xu Yan; Siqi Zhang; Yining Tang; Wei Ji; Chaofan Ji; Yiwei Dai; Beiwei Zhu; Xinping Lin (Food Chemistry, 2026)

Review: Synergistic effects of environmental pollutants: Multiple stressors driving the transmission of vector-borne diseases and the vicious cycle - Tingting Liu; Jia Wang; Minghao Yu; Yining Li; Huan Lin; Dan Deng; Xiaolu Shi; Xiaoping Xiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Chitosan-modified photocrosslinked silk fibroin hydrogels loaded with RA-loaded self-assembled bilayer nanoparticles promote healing of infected wounds - Zheng Sun; Linna Wang; Ye Peng; Dixin Xing; Yining Wang; Sufang Zhang; Chaofan Ji; Xinping Lin; Fengming Dong; Ningbo Qin (Chemical Engineering Journal, 2026)

Antibiotic resistance genes against “last-resort” antibiotics within the One Health framework: Dissemination, mechanisms, and AI-driven opportunities - Yining Wu; Lin Zhu; Na Li; Chuze Lu; Chengdong Zhang; Meizhen Wang (Journal of Hazardous Materials, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

The impact of storage conditions on quality and shelf life of fresh-cut jackfruit: a metabolomics perspective - Yuting Huang; Wenli Zhang; Wanqing Sun; Wenzhu Shen; Yifan Cheng; Yining Xia; Yanjun Zhang; Qiong Lin (Food Chemistry, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Modulating NLRP3 Inflammasome Activity and Enhancing Cortical Synaptic Plasticity: Nanoparticulate Hydrogen’s Role in Relief of Post-traumatic Anxiety-like Behaviors in Rats - Lanxia Wu; Congwen Yang; Yiqin Ding; Xinru Liu; Hao Sun; Xue Li; Yining Lu; Lifen Liu; Qingyang Fu; Min Li; Yingshuai Wang; Yuehan Zhao; et al. (Molecular Neurobiology, 2026)

Preparation of sodium alginate/sodium carboxymethyl cellulose composite coating film and evaluation of its effects on mango preservation - Wei Wang; Jiakai Yu; Yuting Huang; Bai-Jun Li; Wenzhu Shen; Wenli Zhang; Yining Xia; Qiong Lin (Food Chemistry, 2025)

Dual-mode demodulation method for robust underwater acoustic communication - Yining Lin; Yupeng Tai; Chenghao Hu; Yonglin Zhang; Jun Wang; Longxu Wang; Haibin Wang (Ocean Engineering, 2025)

Safranal ameliorates atherosclerosis progression partly via repressing PI3K/Akt and NF-κB signaling pathways in ApoE (−/−) mice - Yining Geng; Manping Song; Bing Huang; Ru Lin; Shiwen Wu; An Lin (Journal of Natural Medicines, 2025)

Konjac glucomannan/ carboxylated cellulose nanofiber-based edible coating with tannic acid maintains quality and prolongs shelf-life of mango fruit - Jiaxin Wang; Mian Qin; Wei Wang; Yining Xia; Guang Wu; Hao Deng; Qiong Lin (Food Chemistry, 2025)

Regulation strategies of microplastics with different particle sizes on cadmium migration processes and toxicity in soil-pakchoi system - Qirui An; Na Zheng; Changcheng Chen; Xiaoqian Li; Yining Ji; Liyuan Peng; Zhifei Xiu; Qiuyan Lin (Journal of Hazardous Materials, 2025)

The interaction of atmospheric boundary layer and PM pollution in Mongolian Plateau: Implication for the threshold control strategy - Simin Yang; Yongjing Ma; Wenyu Zhang; Zhong Lin; Zhenguo Lu; Xingjun Zhou; Yuanzhe Ren; Xinbing Ren; Kecheng Peng; Yulong Tan; Yiming Wei; Masroor Ahmad; et al. (Atmospheric Research, 2025)

Tea Saponins: a Novel Stabilizer for Enhancing the Oral Bioavailability of Albendazole Nanocrystals - Sumin Lan; Kexi Chen; Liqiang Feng; Panle Sima; Xiaoyao Ji; Feihua Wu; Yining Lin (AAPS PharmSciTech, 2025)

Multi-omics analyses reveal mechanism for high resistant starch formation in an indica rice SSIIIa mutant - Yining Ying; Bowen Deng; Lin Zhang; Yaqi Hu; Lei Liu; Jinsong Bao; Feifei Xu (Carbohydrate Polymers, 2025)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Study on formation process and reservoir damage mechanism of blockages caused by polyacrylamide fracturing fluid in production wells - Zhongzheng Xu; Mingwei Zhao; Jiawei Liu; Yiming Zhang; Mingwei Gao; Xuguang Song; Ning Sun; Lin Li; Yining Wu; Caili Dai (Fuel, 2024)

Insights into the influence and mechanism of biomass substrate and thermal conversion conditions on FeN doped biochar as a persulfate activator for sulfamethoxazole removal - Yining Lin; Qiang Ge; Jinquan Wan; Yan Wang; Congyun Zhu (Science of The Total Environment, 2024)

Effect of cell settlement on the electrochemical collision behaviors of single microbes - Hanxin Zhang; Guanyue Gao; Yafei Chen; Lan Lin; Dengchao Wang; Yining Fan; Yanran Liu; Qi Zhao; Jinfang Zhi (Analytica Chimica Acta, 2023)

Free amino acids in response to salinity changes in fishes: relationships to osmoregulation - Ming Huang; Qinfeng Gao; Xiaogang Yang; Wenxin Jiang; Lin Hao; Yining Yu; Yuan Tian (Fish Physiology and Biochemistry, 2023)

Impact of Primary Container Closure System on PS80 Oxidation and the Mechanistic Understanding - Ryan Mould; Peter William Sargent; Yining Huang; Allison L. Fields; Lin Zhang; Fabian Castro Herbert; Stephanie Lynn Stewart; Tingting Wang (Pharmaceutical Research, 2023)

Dynamic change of the carotenoid metabolic pathway profile during oolong tea processing with supplementary LED light - Zixin Ni; Yun Yang; Yining Zhang; Qingcai Hu; Jiaqi Lin; Hongzheng Lin; Zhilong Hao; Yuefei Wang; Jihong Zhou; Yun Sun (Food Research International, 2023)

Starch structural reasons for the effects of SSIIIa deficiency on the textural and digestive properties of cooked rice - Zhongwei Zhang; Yining Ying; Lin Zhang; Gaoxing Dai; Guofu Deng; Jinsong Bao; Feifei Xu (Journal of Cereal Science, 2023)

Application of Deep Learning-Based Object Detection Techniques in Fish Aquaculture: A Review - Hanchi Liu; Xin Ma; Yining Yu; Liang Wang; Lin Hao (Journal of Marine Science and Engineering, 2023)
Automated monitoring and analysis of fish’s growth status and behaviors can help scientific aquaculture management and reduce severe losses due to diseases or overfeeding. With developments in machine vision and deep learning (DL) techniques, DL-based object detection techniques have been extensively applied in aquaculture with the advantage of simultaneously classifying and localizing fish of interest in images. This study reviews the relevant research status of DL-based object detection techniques in fish counting, body length measurement, and individual behavior analysis in aquaculture. The research status is summarized from two aspects: image and video analysis. Moreover, the relevant technical details of DL-based object detection techniques applied to aquaculture are also summarized, including the dataset, image preprocessing methods, typical DL-based object detection algorithms, and evaluation metrics. Finally, the challenges and potential trends of DL-based object detection techniques in aquaculture are concluded and discussed. The review shows that generic DL-based object detection architectures have played important roles in aquaculture.

Bio-inspired superhydrophobic interface of nano-gaseous film for reducing injection pressure in oil reservoirs - Zhongzheng Xu; Mingwei Zhao; Yiming Zhang; Pan Wang; Yining Wu; Lin Li; Xin Cui; Ning Sun; Caili Dai (Chemical Engineering Journal, 2023)

DNA damage response manages cell cycle restriction of senile multipotent mesenchymal stromal cells - Lin Yao; Fanyuan Yu; Yining Xu; Yitian Wang; Yanqin Zuo; Chenglin Wang; Ling Ye (Molecular Biology Reports, 2020)

Spatial and temporal evolution of landfast ice near Zhongshan Station, East Antarctica, over an annual cycle in 2011/2012 - Jiechen Zhao; Qinghua Yang; Bin Cheng; Matti Leppäranta; Fengming Hui; Surui Xie; Meng Chen; Yining Yu; Zhongxiang Tian; Ming Li; Lin Zhang (Acta Oceanologica Sinica, 2019)

Associations between maternal exposure to air pollution and birth outcomes: a retrospective cohort study in Taizhou, China - Lin Ye; Yinwen Ji; Wei Lv; Yining Zhu; Chuncheng Lu; Bo Xu; Yankai Xia (Environmental Science and Pollution Research, 2018)

Asymmetric synthesis and biological activities of natural product (+)-balasubramide and its derivatives - Jun Li; Jianzu Li; Yuan Xu; Yunjie Wang; Luyong Zhang; Li Ding; Yining Xuan; Tao Pang; Hansen Lin (Natural Product Research, 2016)